Dziecko i dzieciństwo – dialektyka konstruktów w dyskursie społecznym i naukowo- -badawczym - Jarosz, Ewa (Studia Edukacyjne, 2020)
Childhood and childhood are socio-cultural constructs whose form has changed in social history and in cultural-geographical space, conditioned by a number of different factors. The interdisciplinary discourse contains numerous proposals for systematizing these constructs based on various specification criteria. The article proposes a general systematization of these constructs in the perspective of their timeliness. The changing image of the child and childhood is of primary importance for the character of social and educational relations between children and adults. It has moreover caused a transformation of the image of research relations. Since the idea of children’s rights came into being, a new paradigm of research – childhood studies – has been developing, characterized by a specific ontological and epistemological dimension as well as its own approach to methodological solutions. These aspects are discussed and presented in the second part of the article.